Sickle cell trait and the risk of Plasmodium falciparum malaria and other childhood diseases - Williams, T; Mwangi, T; Wambua, S; Alexander, N; Kortok, M; Snow, R; Marsh, K (University of Chicago Press, 2005)
Background: The gene for sickle hemoglobin (Hbs) is a prime example of natural selection. It is generally believed that its current prevalence in many tropical populations reflects selection for the carrier form (sickle cell trait [HbAS]) through a survival advantage against death from malaria. Nevertheless, >50 years after this hypothesis was first proposed, the epidemiological description of the relationships between HbAS, malaria, and other common causes of child mortality remains incomplete. Methods: We studied the incidence of falciparum malaria and other childhood diseases in 2 cohorts of children living on the coast of Kenya. Results: The protective effect of HbAS was remarkably specific for falciparum malaria, having no significant impact on any other disease. HbAS had no effect on the prevalence of symptomless parasitemia but was 50% protective against mild clinical malaria, 75% protective against admission to hospital for malaria, and almost 90% protective against severe or complicated malaria. The effect of HbAS on episodes of clinical malaria was mirrored in its effect on parasite densities during such episodes. Conclusions: The present data are useful in that they confirm the mechanisms by with HbAS confers protection against malaria and shed light on the relationships between HbAS, malaria, and other childhood diseases.